Storage and distribution of organic carbon in two natural forest soils and agricultural systems of cacao land use systems in Palenque, Pasaje - Ecuador. - Luna Florin, Alex Dumany (2025)
The comparative analysis of soil organic carbon (COS) in different systems of use is based on the characteristics of the soil associated with the management and conservation of the systems, the study focused on knowing the organic carbon content at different depths in two types of systems of use such as a natural ecosystem and a farm dedicated to cocoa cultivation. Soil samples were collected at the previously selected points and taken to the laboratory for analysis using the Bouyoucos method, which is based on the principle of sedimentation and makes it possible to determine soil texture by establishing the proportions of sand, silt and clay present. In the natural ecosystem (evergreen forest), the COS content at a depth of 0-15 cm is notably higher, reaching 41,76%, increasing to 42,20% at a depth of 15-30 cm. In contrast, in the cocoa agricultural zone, COS levels decrease from 41,92% at a depth of 0-15 cm to 39,56% at a depth of 15-30 cm. These findings underline the influence of soil depth and type of soil use on the distribution of organic carbon. The natural ecosystem has a superior capacity for organic carbon storage, due to the natural conditions that promote soil fertility and productivity.